STRATEGI KOMUNIKASI PEMAIN BOLA VOLI PUTRI TERHADAP TINGKAT KERJA SAMA TIM KLUB ASVI_VC - Khulud; Murniati, Sri; Prabowo, Bangkit Yudho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the communication strategies of female volleyball players in improving teamwork in the ASVI_VC club. The background of this study is based on the persistent obstacles in coordination between players, such as misunderstandings when receiving the ball, lack of communication on the field, and a suboptimal understanding of each player's role, which impacts the decline in team cohesion. Therefore, effective communication is a crucial factor in supporting the success of team play. This study uses a qualitative approach with descriptive methods to explore in depth the forms of communication that occur between players during training and matches. The research subjects consisted of five female athletes who are active in club activities. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation. Data analysis used a model that includes data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that verbal and nonverbal communication play a crucial role in improving teamwork. Verbal communication such as giving directions, signals, and motivation helps clarify tasks and improve game coordination. Meanwhile, nonverbal communication such as hand signals, eye contact, and body movements helps speed up responses between players on the field. In addition, effective communication can build trust, strengthen interpersonal relationships, and improve team cohesion. Thus, a good communication strategy has a positive impact on improving the team's performance and success in matches.